A phase change thermal storage material and its performance for floor electric heating system. (March 2023) - Wang, Bin; Zhou, Wenhe; Wu, Jianyun; Sun, Lei; Wang, Meng; Zhang, Wenxiang
Abstract: The heat storage and release characteristics of the traditional electric heating floor can be improved by introducing phase change material (PCM), which can help to use the solar photovoltaic system (PV), shift peaks and valleys of electric power and improve indoor thermal comfort. In this study, the composite phase change materials (CPCMs) are made of paraffin (PA) and expanded graphite (EG) with different sizes and tested firstly. The results show that 100 mesh, 200 mesh and 800 mesh EG can accommodate 75 %, 85, and 95 % PA at most, respectively. Subsequently, the samples of electric heating floor of thermal storage (BPCM) are made by combining CPCM into concrete and tested, including the characteristics of compressive strength and heat storage and release. The heat capacity of BPCM is greater than that of ordinary concrete, and its average temperature difference in the heat storage and release stage can be reduced by 2.84 °C. The addition of CPCM has a critical influence on the compressive strength of BPCM, and BPCM compressive strength reduces to 25.56 MPa when the volume fraction of CPCM is 30 %, which is 31.58 % lower than that of pure concrete. This research will promote the application of house solar PV system. Highlights: The paraffin/expand graffiti composite phase change material(CPCM) has large latent heat. The encapsulation of expanded graphite effectively solves the problem of paraffin leakage. The paraffin/expand graffiti CPCM has excellent thermal stability and cycle stability. Phase change thermal storage electric floor heating has good thermal performance. The strength of phase change thermal storage electric floor heating meets the requirements of the specification.